On some Afrotropical Harpalus, with description of two new species, and remarks on Hypharpax australis (Coleoptera: Carabidae): misidentification, mislabeling, and introduction to the Australian region - Kataev, Boris M. (Zootaxa, 2021)
New data on taxonomy of several Afrotropical species of Harpalus Latreille, 1802 are provided, with special attention to the species recorded outside the African continent. Two new species from East Africa are described: H. pseudoasemus sp. n. from Tanzania and Kenya (type locality: Oldonyo Dambu, 15 km north of Arusha, Tanzania), and H. merkli sp. n. from Ethiopia (type locality: Chercher). Harpalus impressus Roth, 1851, H. asemus Basilewsky, 1947, H. fuscoaeneus Dejean, 1829, H. australasiae Dejean, 1829, and H. parvulus Dejean, 1829 are re-described based on the types and additional material, and the diagnostic characters of Hypharpax australis (Dejean, 1829) are given. Harpalus australasiae sensu Larochelle & Larivière, 2005 (non Dejean, 1829) is treated as conspecific with the Afrotropical H. parvulus which was introduced to Australia and New Zealand. The genus Anisochirus Jeannel, 1946, stat. resurr. is restored for most of the Madagascan and Mascarene species included previously in Harpalus. The members of this genus differ from those of Harpalus in having glabrous paraglossae. The status and taxonomic position of Anisochirus is discussed. The following synonymies are proposed: Harpalus impressus Roth, 1851 = H. sundaicus Schauberger, 1933, syn. n., and H. asemus Basilewsky, 1947 (January 30) = H. hamasiensis G. Müller, 1947 (September 30), syn. n. Lectotypes are designated for H. impressus and H. fuscoaeneus.